Photocatalytic degradation of methylene blue by a cocatalytic PDA/TiO2 electrode produced by photoelectric polymerization. Issue 44 (10th July 2020) - Guo, Zehui; Wang, Guoqing; Fu, Haiqing; Wang, Peiqing; Liao, Jianhe; Wang, Aimin
Abstract : This study reports a new method for photocatalysts to degrade organic dyes on organic semiconductors. Abstract : This study reports a new method for photocatalysts to degrade organic dyes on organic semiconductors. A novel strategy is reported to form TiO2 nanorod (NR)/polydopamine (PDA) electrodes with a photoelectric polymerization strategy for PDA (pep-PDA) to produce cocatalytic electrodes. Amperometric i – t curves and UV-vis diffuse reflectance spectra were recorded and showed that compared with traditional self-polymerization (sp-PDA) and electropolymerization (ep-PDA), TiO2 NR/pep-PDA exhibited an enhanced photocatalytic activity under visible light. As expected, TiO2 NR/pep-PDA showed a significant improvement for the degradation of methylene blue (MB) under visible light, which can be attributed to the strong absorption of PDA in the visible light region and the more complete and uniform coverage of the TiO2 NRs by the pep-PDA film. This study not only proposes a novel and highly efficient way to load PDA on TiO2 NRs but also provides useful insights for the loading of other photocatalysts on organic semiconductors to degrade organic dyes.